2021
DOI: 10.3389/fgene.2021.764270
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Inhibitor of Apoptosis Protein Expression and Prognostic Significance in Non–Small Cell Lung Cancer

Abstract: Inhibitors of apoptosis proteins (IAPs) have been associated with tumor development and progression by affecting apoptosis through cell death signaling pathways. To date, eight IAPs (BIRC1–8) have been identified in mammalian cells. However, the role of IAPs in non–small cell lung cancer (NSCLC) development and progression has not been explored in depth. In this study, we used public datasets and bioinformatics tools to compare the expression, prognostic significance, and function of IAPs in NSCLC and its subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…BIRC5 is a member of the inhibitors of apoptosis (IAP) gene family, which encodes negative regulatory proteins that prevent apoptotic cell death. Unlike other IAPs, BIRC5 expresses intensely in most tumors, including LUAD and LUSC [ 55 ], and it could serve as a predictive biomarker for NSCLC, especially for LUAD [ 56 ], but does not express or only expresses at low levels in most normally differentiated tissues [ 57 ], and down-regulated BIRC5 was positively associated with NSCLC survival time [ 58 ]. Cell division cycle 6 ( CDC6 ) is an important regulator of DNA replication, and there is evidence that silencing of CDC6 may lead to G1 phase arrest [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…BIRC5 is a member of the inhibitors of apoptosis (IAP) gene family, which encodes negative regulatory proteins that prevent apoptotic cell death. Unlike other IAPs, BIRC5 expresses intensely in most tumors, including LUAD and LUSC [ 55 ], and it could serve as a predictive biomarker for NSCLC, especially for LUAD [ 56 ], but does not express or only expresses at low levels in most normally differentiated tissues [ 57 ], and down-regulated BIRC5 was positively associated with NSCLC survival time [ 58 ]. Cell division cycle 6 ( CDC6 ) is an important regulator of DNA replication, and there is evidence that silencing of CDC6 may lead to G1 phase arrest [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…BIRC2 degradation in cells leads to RIPK1 de-ubiquitination and autocrine TNF-α signaling, which trigger either necroptotic or apoptotic cell death [23]. Studies have reported that BIRC2 is overexpressed in many cancers including cervical cancer, breast cancer, lung cancer, and bladder cancer, which can lead to resistance to treatment or signi cantly worse outcomes [21,22,24,25].…”
Section: Discussionmentioning
confidence: 99%